(untitled) (Clinics, 2013)
OBJECTIVE: We tested the reproducibility of changes in the ambulatory blood pressure (BP) from the initial values, an indicator of BP reactivity and cardiovascular health outcomes, in young, healthy adults. METHOD: The subjects wore an ambulatory BP monitor attached by the same investigator at the same time of day until the next morning on two different days (day 1 and day 2) separated by a week. We compared the ambulatory BP change from the initial values at hourly intervals over 24 waking and sleeping hours on days 1 and 2 using linear regression and repeated measures analysis of covariance. RESULTS: The subjects comprised 88 men and 57 women (mean age±SE 22.4±0.3 years) with normal BP (118.3±0.9/69.7±0.6 mmHg). For the total sample, the correlation between the ambulatory BP change on day 1 vs. day 2 over 24, waking, and sleeping hours ranged from 0.37-0.61; among women, the correlation was 0.38-0.71, and among men, it was 0.24-0.52. Among women, the ambulatory systolic/diastolic BP change was greater by 3.1±1.0/2.4±0.8 mmHg over 24 hours and by 3.0±1.1/2.4±0.8 mmHg over waking hours on day 1 than on day 2. The diastolic ambulatory BP change during sleeping hours was greater by 2.2±0.9 mmHg on day 1 than on day 2, but the systolic ambulatory BP change during sleeping hours on days 1 and 2 did not differ. Among men, the ambulatory BP change on days 1 and 2 did not differ. CONCLUSION: Our primary findings were that the ambulatory BP change from the initial values was moderately reproducible; however, it was more reproducible in men than in women. These results suggest that women, but not men, may experience an alerting reaction to initially wearing the ambulatory BP monitor.